Analytical Review of Occupational Health Problems among Rice Mill Workers: The Role of Health Education - Ogbuinya, Nkiru; Ohuruogu, Ben (NIGERIAN JOURNAL OF HEALTH PROMOTION, 2017)
An ill workforce can only lead to low work output and invariably lead to an ill economy. Reports have it that over 170 days lost to absence of workers from work environments have been attributed to the workers’ exposure to physical, chemical or biological agents in their work places. Among rice mill workers, these have led to various health problems ranging from musculoskeletal pains to conjunctivitis, pterygium, oesinophilis, leucosytosis, skin allergy and reduced PEFR among others. This paper reviewed the health problems, prevention, control and there after discussed the role of health education in dealing with the occupational health problems. The paper concluded that the health problems among the rice mill workers are remediable and as such, every effort should be garnered towards ensuring proper Occupational Health and Safety (OHS) procedures/practices within the work environments. The paper, thus, recommended among others, immediate deployment of health educators to sensitize the workers and their employers on the prevailing health problems in their work places thus, paving the way for disease early detection, prevention and control. These in effect would reduce morbidity and mortality rates among the rice mill workers.